Properties of the hybrid glauconite/polyaniline composites synthesized in the aqueous citrate acid solutions - Yatsyshyn, Mykhaylo; Makogon, Viktoriia; Reshetnyak, Oleksandr; Demchenko, Pavlo; Dumanchuk, Nataliya; Stadnyk, Yuriy (Publishing House of Lviv Polytechnic National University, 2016)
For the first time the series of the composites of aniline and natural mineral glauconite with different ratio of components has been synthesized by oxidation of aniline by ammonium peroxydisulfate in 0.5 M citrate acid aqueous solutions in the presence of dispersion of mineral filler. X-ray phase analysis confirms the amorphous-crystalline structure of produced composites. Results of FTIR spectral analysis show that the samples contain PAn in the form of emeraldine salt and also indicate the presence of weak interfacial interaction between particles of glauconite and polyaniline macrochains in the result of the formation of hydrogen bonds. The results of thermogravimetric analysis of synthesized samples with different composition showed that thermal stability of composites samples increases under the higher glauconite content. It is determined that the thermodestruction of composites is a multistage process. The electric conductivity of composites produced samples with high content of polyaniline is on the level of pure polyaniline. The specific magnetization of synthesized composites in applied magnetic field increases to the value which is characteristic of the pure mineral under the increasing of glauconite content in the composite. Окисненням аніліну пероксодисульфатом амонію в 0,5 М водних розчинах цитратної кислоти за наявності природного мінералу глауконіту синтезовано ряд композитів із різним співвідношенням глауконіт/поліанілін. За допомогою рентгенофазового аналізу показано, що структура отриманих композитів є аморфно-кристалічною. Результати ІЧ-ФП спектрального аналізу зразків показали, що зразки містять ПАн у вигляді емеральдинової солі, а також вказують на наявність слабкої міжфазової взаємодії між частинками глауконіту і макроланцюгів поліаніліну внаслідок утворення водневих зв’язків. Порівняння результатів дериватографічних досліджень синтезованих зразків з різним складом показало, що зі збільшенням вмісту глауконіту підвищується термічна стійкість зразків композитів. Виявлено, що процес термодеструкції композитів є багатостадійним. Питома електропровідність отриманих композитів при високих вмістах поліаніліну знаходиться на рівні таких показників, як для чистого поліаніліну. Питома намагніченість отриманих композитів в прикладеному магнітному полі при збільшенні вмісту глауконіту в композитах зростає до значень близьких для чистого мінералу.
Властивості гібридних композитів глауконіт/поліанілін, синтезованих у водних розчинах цитратної кислоти
Keywords: polyaniline; glauconite; composites; X-ray phase analysis; thermal stability; electric conductivity; specific magnetization; поліанілін; глауконіт; композити; структура; термічна стабільність; електропровідність; питома намагніченість